Essential oil from the discarded peels of the fruit of Hymenaea courbaril L. as larvicidal opposite Aedes aegypti (Research, Society and Development, 2020)
This study aimed to chemically characterize and evaluate the larvicidal activity of essential oil (EO) extracted from the peels of the commonly discarded fruit of Hymenaea coubaril L. For EO extraction, the hydrodistillation technique was used in a modified Clevenger extractor system. The chemical constituents were obtained by Gas Chromatography coupled to mass spectrometry (GC/MS). Larvae of Aedes aegypti were submitted to essential oil solutions at concentrations of 10-100 mg L-1, where larvae mortality was evaluated and LC50 was determined. β-ocimeno was quantified as the majority in the EO. It was observed the action of EO as larvicidal where the LC50 of 16.6 mg L-1. The results obtained allowed us to conclude that the EO studied presented efficient larvicidal activity against the larvae of Aedes aegypti, being important and encouraged its use and application.